The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fncel.2017.00202
|View full text |Cite
|
Sign up to set email alerts
|

Development of Serotonergic Fibers in the Post-Natal Mouse Brain

Abstract: Serotonin (5-HT)-synthetizing neurons, which are confined in the raphe nuclei of the rhombencephalon, provide a pervasive innervation of the central nervous system (CNS) and are involved in the modulation of a plethora of functions in both developing and adult brain. Classical studies have described the post-natal development of serotonergic axons as a linear process of terminal field innervation. However, technical limitations have hampered a fine morphological characterization. With the advent of genetic mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 34 publications
(56 reference statements)
3
72
0
Order By: Relevance
“…We observed positive concordant results between the TIAM2S expression and serotonin level in this study. Previously, studies have shown the serotonergic fiber development and growth in the postnatal brain participates in enormous and progressive functions in the brain . Given that the density of serotonergic fibers is linked directly to serotonin levels, the changing of neuron number and neurite length of serotonergic neuron thus may explain the alteration of overall serotonin level found in our study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We observed positive concordant results between the TIAM2S expression and serotonin level in this study. Previously, studies have shown the serotonergic fiber development and growth in the postnatal brain participates in enormous and progressive functions in the brain . Given that the density of serotonergic fibers is linked directly to serotonin levels, the changing of neuron number and neurite length of serotonergic neuron thus may explain the alteration of overall serotonin level found in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Previously, studies have shown the serotonergic fiber development and growth in the postnatal brain participates in enormous and progressive functions in the brain. 69,70 Given that the density of serotonergic fibers is linked directly to serotonin levels, the changing of neuron number and neurite length of serotonergic neuron thus may explain the alteration of overall serotonin level found in our study. Nevertheless, the molecular mechanism underlines TIAM2S-mediated controls to alter serotonin level remain unclear and is of interest for further investigation.…”
Section: Regulation Of the Developing Serotonergic Fibers By Tiam2smentioning
confidence: 67%
“…Therefore, in the LA the glutamate release in response to paired pulse stimulation seems to be reduced in TPH2 −/− mice. Besides differences in release probability differences in PPF in the amygdala and the hippocampus, observed in our study might be also due to differences in the density of serotonergic fibers in the CA1 region and the LA (Maddaloni et al, ).…”
Section: Discussionmentioning
confidence: 54%
“…Data points represent averaged amplitudes (mean AE SEM) normalized with respect to baseline values. Representative traces were recorded 5 min prior to tetanus (dashed lines) and 60 min after HFS/TBS stimulation (solid lines) observed in our study might be also due to differences in the density of serotonergic fibers in the CA1 region and the LA (Maddaloni et al, 2017).…”
Section: Discussionmentioning
confidence: 68%
“…The distinct phenotypes of prenatal-only versus postnatally-extended FLX pups may be mediated by differences in 5HT system development that occurs at these different periods. While 5HT axons reach their targets by birth, terminal field development occurs postnatally (Maddaloni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%